(untitled) (Bioresearch Communications, 2022)
Background: Consultant Couple Interactive (CCI) session is an interactive session held weekly between service provider and the infertile couple. Objective: The purpose of this study was to assess the effect of CCI sessions on fertility outcome. Methodology: This mixed method study was conducted from May 2009 to August 2012. The samples were collected from a primary care center at Bheramara upazila of district of Kushtia on couples attending during that period. The qualitative part was performed on couples by asking open-ended questions as well as the focus group discussion (FGD). For quantitative part, a preformed data collection sheet (questionnaire) was used to collect data through face to face interview. Results: A total number of 275 couples were studied. For qualitative study, 55(20%) couples were selected, of them 41 participated. In a single focused group up to 6 (12 persons) couples were included. Among the 41 couples, 61% had primary and in 39% had secondary infertility. All the respondents were exposed to CCI sessions but 186 (67.6%) were treated with only with CCI. Out of the remaining 53 (19.3%), needed ovulation inducing oral drugs, 5 (1.8%) were treated with metformin and the others required medical and surgical treatments in different combination according to need. Out of 275 respondents, 112 (40.7%) conceived and among the conceived group, 72 (64.3%) conceived only following CCI. From the seven FGDs, it was revealed that most of the couples followed the advices provided during CCI session, majority were able to improve the relationship among partners and two third of the respondents could relieve 75% of environmental pressure exerted on them. Conclusion: The consultant couple interactive session has significant effect on fertility outcome among infertile couples. Bioresearch Commu. 8(2): 1143-1148, 2022 (July)